Some considerations on the influence of economic liberalism in the May Revolution of 1810 in Buenos Aires, Argentina - Blanco, Alfredo Félix (Iberian Journal of the History of Economic Thought, 2015)
The revolutionary process of May 1810 in Buenos Aires, capital of the Viceroyalty of the Río de la Plata, occurred within the context of the French Revolution, the United States’ struggle for independence and various changes in the European countries’ economies. Liberal ideas played an essential role, and the opinions of Belgrano, Vieytes and Moreno, among others, are the key to understanding the economic perspectives of the revolutionary men. Late mer-cantilists, physiocrats and classical economists marked these men’s economic thought. The purpose of this paper is to review these intellectual influences on the leaders of the May Revolution.